2009
DOI: 10.1074/jbc.m109.005082
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of the Tetramer Organization of Malic Enzyme

Abstract: Malic enzyme has a dimer of dimers quaternary structure in which the dimer interface associates more tightly than the tetramer interface. In addition, the enzyme has distinct active sites within each subunit. The mitochondrial NAD(P) ؉ -dependent malic enzyme (m-NAD(P)-ME) isoform behaves cooperatively and allosterically and exhibits a quaternary structure in dimertetramer equilibrium. The cytosolic NADP ؉ -dependent malic enzyme (c-NADP-ME) isoform is noncooperative and nonallosteric and exists as a stable te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
0
32
0
3
Order By: Relevance
“…With regard to functional structure organization, it has been found that the NADP + -dependent isoform of human ME with a stable tetramer behaves in a non-cooperative and non-allosteric manner, whereas the human NAD + -dependent isoform performs cooperatively and allosterically (Hsieh et al, 2009). For the latter isoform, the dissociation of subunits at the dimer or tetramer interface reduces the enzyme's activity by influencing malate binding cooperation and fumarate responsiveness (Hsieh et al, 2009). It is interesting and unclear how this structure of the NADP + -dependent ME of Mu.…”
Section: Comparison Of 3d Structural Models Of Mes Between Clusters Dmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to functional structure organization, it has been found that the NADP + -dependent isoform of human ME with a stable tetramer behaves in a non-cooperative and non-allosteric manner, whereas the human NAD + -dependent isoform performs cooperatively and allosterically (Hsieh et al, 2009). For the latter isoform, the dissociation of subunits at the dimer or tetramer interface reduces the enzyme's activity by influencing malate binding cooperation and fumarate responsiveness (Hsieh et al, 2009). It is interesting and unclear how this structure of the NADP + -dependent ME of Mu.…”
Section: Comparison Of 3d Structural Models Of Mes Between Clusters Dmentioning
confidence: 99%
“…For example, a human NAD(P) + -dependent ME has dual specificity for the dinucleotide cofactor NAD + and NADP + in the binding of malate, and is regulated by fumarate and ATP, whereas another isoform is specific for NADP + . Additionally, distinct roles of tetramer organization have been reported for the NADP + -and NAD + -dependent ME isoforms (Yang et al, 2002;Tao et al, 2003;Hsieh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Роль данного фермента в клеточном метаболизме определяется, прежде всего, восстановлением НАДФ до НАДФН, ко-торый затем используется в синтетических кле-точных процессах [11,18]. Снижение активности НАДФМДГ может приводить к недостаточному образованию восстановительной формы цито-плазматического НАДФН и недостатку субстра-тов для биосинтеза жирных кислот, а это может определять снижение реакций липидного обме-на в клетке.…”
Section: Discussionunclassified
“…Кроме того, у детей основной группы в лимфо-цитах периферической крови наблюдается повышение содержания малик-фермента, шунтирующего «медлен-ные» реакции цикла Кребса и являющегося ключевым ферментом липидного анаболизма [13].…”
Section: Discussionunclassified